Fine patterned YBCO films grown on flexible nickel–tungsten substrates by photosensitive sol–gel method. (March 2022) - Li, Limin; Zhao, Gaoyang; Lei, Li; Yan, Fuxue; Deng, Bo; Li, Chengshan
Highlight: The fine patterned YBCO films were prepared on flexible NiW substrates. The good epitaxial growth relationship were achieved at the interface. 3 YBCO patterns can withstand bending deformation and the superconductivity is good. Abstract: In recent years, efforts devoted to the study of processing technologies for flexible devices have been increasing significantly. The fabrication of YBa2 Cu3 O7-x (YBCO) fine patterns on flexible nickel–tungsten (NiW) substrates is beneficial for the application of flexible superconducting electronic devices. The most challenging task is the simultaneous achievement of fine patterning and biaxial epitaxial growth of YBCO films on NiW substrates. This work reports the application of the photosensitive sol–gel lithography in combination with an all chemical deposition process to prepare fine patterned YBCO films on NiW substrates using gadolinium-doped lanthanum zirconate (LGZO) films as buffer layers. High-quality patterned YBCO films were epitaxially grown on LGZO–buffered NiW substrates, and the well-continuous YBCO patterns on flexible substrates could withstand bending deformations. The superconductivity remains good after the mechanical bending deformation process. These results are useful as guidance for the application of flexible superconducting devices. Graphical abstract: Image, graphical abstract